Mast cells in the kidney biopsies of pediatric patients with lupus nephritis - Santos,Stéfany Silva (2020)
ABSTRACT Introduction: Mast cells may be involved in inflammation and contribute to the onset of fibrosis in lupus nephritis (LN). Objective: This study aimed to correlate the presence of mast cells in kidney biopsy specimens of pediatric patients with LN with activity (AI) and chronicity (CI) indices and assess how effectively mast cells may be used as a prognostic factor. Method: The study included 40 patients aged 6-18 years diagnosed with LN at the Renal Disease Service of the Federal University of Triângulo Mineiro between 1996 and 2015. Workup and epidemiological data were evaluated vis-à-vis AI, CI, and mast cell counts (MCC). Results: Significant positive correlations were found between mast cell counts (MCC) and AI (p = 0.003; r: 0.66) and MCC and CI (p = 0.048; r: 0.48). The ROC curve showed that mast cells were highly sensitive and specific in the differentiation of patients with an AI > 12 from individuals with an AI ≤ 12. Serum creatinine levels were higher in individuals with class IV LN than in patients with class V disease [1.50 (0.40-20.90) vs. 0.70 (0.62-0.90), p = 0.04]. Blood urea nitrogen had a positive significant correlation with MCC (p = 0.002; r: 0.75). A trend toward a negative correlation was observed between MCC and serum albumin (p = 0.06; r: -0.5459). Kidney biopsies of patients with nephrotic syndrome had higher MCC [2.12 (0.41-5.140) vs. 0.53 (0.0-3.94), p = 0.07]. Conclusion: Inflammatory cell infiltration and morphological differences between cell types in the inflammatory infiltrate are relevant factors in the assessment of the LN. Mast cell analysis and AI/CI assessment may be relevant prognostic indicators for pediatric patients with LN.